SARS-CoV-2–specific mucosal immune response in vaccinated versus infected children - Conti, Maria Giulia; Piano Mortari, Eva; Nenna, Raffaella; Pierangeli, Alessandra; Sorrentino, Leonardo; Frasca, Federica; Petrarca, Laura; Mancino, Enrica; Di Mattia, Greta; Matera, Luigi; Fracella, Matteo; Albano, Christian; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The anti-COVID-19 intramuscular vaccination induces a strong systemic but a weak mucosal immune response in adults. Little is known about the mucosal immune response in children infected or vaccinated against SARS-CoV-2. We found that 28% of children had detectable salivary IgA against SARS-CoV-2 even before vaccination, suggesting that in children SARS-CoV-2 infection may be undiagnosed. After vaccination, only RBD specific IgA1 significantly increased in the saliva. Conversely, infected children had significantly higher salivary RBD-IgA2 compared to IgA1, indicating that infection more than vaccination induces a specific mucosal immune response in children. Future efforts should focus on development of vaccine technologies that also activate mucosal immunity.